Center field shot : a history of baseball on television - Walker, James R. (University of Nebraska Press, 2008)
Center Field Shot traces a sometimes contentious but mutually beneficial relationship from the first televised game in 1939 to the new era of Internet broadcasts, satellite radio, and high-definition TV, considered from the perspective of businessmen collecting merchandising fees and advertising rights, franchise owners with ever more money to spend on talent, and broadcasters trying to present a game long considered "unfriendly" to television. Ultimately the association of baseball with television emerges as a reflection ofperhaps even a central feature ofAmerican culture at large